2011
DOI: 10.1159/000334172
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Survival post Surgery for Patients with Gastrointestinal Stromal Tumors

Abstract: Background: Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms located in the alimentary tract. Our aim was to assess the influence of prognostic factors on survival in patients surgically treated for GISTs. Study: One hundred and five patients treated between January 1989 and December 2008 were available for study. A retrospective analysis of prognostic factors (age, gender, mitotic index, tumor location, tumor size, risk of malignant behavior, and coexisting other neoplasm) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 70 publications
3
7
0
Order By: Relevance
“…The most common site of GIST in our study was the stomach, which is in keeping with most clinical reports [ 3 , 20 , 32 34 ]. The question still remains, is tumor location of any significance as a prognostic factor?…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The most common site of GIST in our study was the stomach, which is in keeping with most clinical reports [ 3 , 20 , 32 34 ]. The question still remains, is tumor location of any significance as a prognostic factor?…”
Section: Discussionsupporting
confidence: 91%
“…The question still remains, is tumor location of any significance as a prognostic factor? Some studies insist that it does [ 1 , 20 , 21 , 32 – 42 ], while others say it does not hold any statistical relevance [ 43 47 ]. Our data correspond more to the latter one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through multivariate analysis, higher mitotic rate and tumor metastasis or local invasion prior to treatment were revealed to be associated with poor survival in GIST patients, and non-gastric disease location was associated with tumor recurrence, which is consistent with the results of previous studies ( 16 ). Similarly, one British study ( 17 ) identified high mitotic index as an independent poor prognostic factor in these patients. Miettinen and Lasota ( 37 ) also demonstrated that small intestinal GISTs behave more aggressively than gastric GISTs, and small intestinal GISTs tend to be larger and more advanced at diagnosis.…”
Section: Discussionmentioning
confidence: 80%
“…The following details of these patients were collected: Age, sex, symptoms and signs, preoperative investigations, surgical details, pathology and follow-up data. The tumor site was analyzed according to previous classification methods ( 16 , 17 ). Preoperative investigations comprised radiological and endoscopic examinations, including gastroscopy, abdominal CT, MRI, colonoscopy, small intestinal endoscopy, capsule endoscopy and positron emission tomography (PET)-CT.…”
Section: Methodsmentioning
confidence: 99%